The Perspective of Islamic Index Performance in Indonesia: A Conceptual Paper - Eky Ermal M (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
This paperis objected to know the development studies related to the comparative Islamicindex. The perspectiveof this study showed inconsistency results, supporting studies accordingto the portfolio theory, the risk-return performance studies by focusing on comparative between Islamic funds or indices against their benchmark. The purpose of this study to know the performance Islamic investment risk-return profile and risk adjusted return measures whether Islamic funds outperform, underperform, or similar performanceagainst the conventional benchmark. Therefore, from this conceptual paper the Indonesian perspectiveof Islamic index describes not better than conventional benchmarking.